Ginástica geral como conteúdo da educação física na BNCC : relações com a linguagem corporal no processo educativo de estudantes do ensino fundamental I - Ferreira, Eder Martins (2024)
General Gymnastics is a comprehensive modality that comes from Gymnastics and is part of the Thematic Units of Physical Education in the National Common Curricular Base. This manifestation of the Body Culture of Movement involves a series of elements of dance, folk expressions, juggling, acrobatics and free and creative activities. Due to this range of possibilities, this modality is highly relevant to the school environment. Therefore, what justified the proposition of this study, which developed an intervention plan in Physical Education classes, was to identify the effects of General Gymnastics content on learning, analyzing and understanding such effects within the scope of body language, expressiveness and construction of new movements in students in the early years of elementary school. The methodology adopted was a qualitative approach, with the application of procedures and assumptions of pedagogical intervention research. 27 students from the 4th year of Elementary School at Escola Novo Horizonte, in Primavera do Leste-MT, participated in the research. Data collection was carried out over a period of two months, corresponding to one academic two-month period, with twelve interventions in total, in which we had as research instruments: the field diary and the exit questionnaire. The intention was to, with a script of actions, demonstrate basic movements, in a varied range of gestures, of the modalities within Gymnastics for All to the students and, challenge them to do the same at first and after creating some movement to based on the given movement, thus analyzing your creative and autonomous capacity for expression and body language. We noticed, through the information collected, that the modality brought significant evolutions and improvements in the children's expressive skills, perceptions and ways of feeling their bodies and movements to each class, facilitating the development of initiative, autonomy and enthusiasm for learning.